1996
DOI: 10.3758/bf03201103
|View full text |Cite
|
Sign up to set email alerts
|

Tests of the separate retrieval of item and associative information using a frequency-judgment task

Abstract: The degree to which item and associative information can be distinguished at retrieval was assessed using a frequency-judgment task. Words were shown various numbers of times individually and as members of word pairs. At test, subjects judged the frequency of the word pairs and a word's frequency as an individual item, its frequency as a member of word pairs, or the combined frequency of the word. Subjects made all of these judgments with considerable accuracy. The frequency of presentations in the nontarget f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…As discussed earlier, SR and AR are differentially sensitive to instructions (Hockley & Cristi, 1996a), have different forgetting rates (Hockley, 1992), and have different rates of improvement with study time (Clark & Shiffrin, 1992). Judgments of frequency indicate that people are generally able to make separate judgments for pairs and singles, even when they have words in common (Hockley & Cristi, 1996b). The present results fit nicely with this research, providing additional evidence for the separation of items and associations during both storage and retrieval.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As discussed earlier, SR and AR are differentially sensitive to instructions (Hockley & Cristi, 1996a), have different forgetting rates (Hockley, 1992), and have different rates of improvement with study time (Clark & Shiffrin, 1992). Judgments of frequency indicate that people are generally able to make separate judgments for pairs and singles, even when they have words in common (Hockley & Cristi, 1996b). The present results fit nicely with this research, providing additional evidence for the separation of items and associations during both storage and retrieval.…”
Section: Discussionsupporting
confidence: 79%
“…However, the array of strategies used in free recall makes it difficult to come to definitive conclusions concerning the source of interference effects. Hockley and Cristi (1996b) had participants study single items and/or pairs that were repeated various numbers of times and in various combinations. In different experiments, a single item could be repeated as both a single and as part of a pair, only as part of a pair, or as part of several different pairs.…”
mentioning
confidence: 99%
“…Exactly this result has been found (Clark & Shiffrin, 1987;Gronlund & Ratcliff, 1989;Cohn & Moscovitch, 2007), even when associative encoding is discouraged (Jou, 2010). In tasks that require separate judgments for the item and associative content of a pair (Hockley & Cristi, 1996b;Buchler et al, 2008Buchler et al, , 2011, participants could rely on the different mismatch signals to make their judgments, although the holistic match would continue to introduce a bias, exactly as has been reported.…”
Section: Tasksmentioning
confidence: 56%
“…Criss and Shiffrin (2005) showed that list discrimination can rely on higherorder relationships among events, rather than only relying on simple associations between items and the lists in which they occurred. As the researchers pointed out, several studies have attempted to distinguish a simple-associations assumption from a higher-order-relationships assumption, with results typically favoring the assumption of higher-order relationships (e.g., Hockley & Cristi, 1996). Hintzman (2004) has described ways in which the results produced by recollection of remindings dictate changes in models of memory, including his own MINERVA model.…”
Section: Discussionmentioning
confidence: 99%